2011
DOI: 10.1002/aqc.1211
|View full text |Cite
|
Sign up to set email alerts
|

Reference vs. present-day condition: early planning decisions influence the achievement of conservation objectives

Abstract: ABSTRACT1. A vast scientific literature has been devoted to identifying the best way to represent biodiversity for conservation in the last decade. Methods exist for deciding how to use scarce information and avoid omission and commission errors. The effect of these errors on reserve efficiency does not arise only from the accuracy of data representing conservation features, as usually considered. There are also several underlying assumptions associated with the type of data used that might affect accuracy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Another strategy was followed by Sealey et al (2014), who estimated cumulative impact scores in coastal ecosystems due to physical restructuring, destructive uses, coastal development, and alien plant invasions, evaluating high-score areas as non-priority for conservation actions. One approach followed by some studies was to integrate alien species in the cost function of MARXAN (Hermoso et al, 2011(Hermoso et al, , 2013Lawrence et al, 2011) or ZONATION (Stewart et al, 2017), which was aimed to be minimized in the prioritization process. Specifically, Hermoso et al (2011) modeled the distribution of alien freshwater fish in the study area and used the modeled abundance as a surrogate of the cost of management actions to control invasive alien species.…”
Section: Approaches Applied To Address Biological Invasions In Consermentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy was followed by Sealey et al (2014), who estimated cumulative impact scores in coastal ecosystems due to physical restructuring, destructive uses, coastal development, and alien plant invasions, evaluating high-score areas as non-priority for conservation actions. One approach followed by some studies was to integrate alien species in the cost function of MARXAN (Hermoso et al, 2011(Hermoso et al, , 2013Lawrence et al, 2011) or ZONATION (Stewart et al, 2017), which was aimed to be minimized in the prioritization process. Specifically, Hermoso et al (2011) modeled the distribution of alien freshwater fish in the study area and used the modeled abundance as a surrogate of the cost of management actions to control invasive alien species.…”
Section: Approaches Applied To Address Biological Invasions In Consermentioning
confidence: 99%
“…One approach followed by some studies was to integrate alien species in the cost function of MARXAN (Hermoso et al, 2011(Hermoso et al, , 2013Lawrence et al, 2011) or ZONATION (Stewart et al, 2017), which was aimed to be minimized in the prioritization process. Specifically, Hermoso et al (2011) modeled the distribution of alien freshwater fish in the study area and used the modeled abundance as a surrogate of the cost of management actions to control invasive alien species. Hermoso et al (2013) focused on the identification of refugia for freshwater fish biodiversity conservation, and avoided planning units in poor condition by integrating condition in the cost function of MARXAN.…”
Section: Approaches Applied To Address Biological Invasions In Consermentioning
confidence: 99%
“…Similarly, Hermoso et al . () found that the use of minimally disturbed vs. present‐day scenarios of fish species distributions in an Iberian river basin led to very different recommendations for identifying priority conservation areas. Here, we investigate the impacts of using historical vs. present‐day reference conditions to set recovery targets for zooplankton communities in lakes with severe and chronic industrial contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Trading off total area needed versus unprotected upstream area sensu Hermoso et al . (b), we decided to use CSM=1 for further analysis.…”
Section: Resultsmentioning
confidence: 99%